Adverse Selection, Commitment, and Renegotiation: Extension to and Evidence from Insurance Markets - Dionne, Georges; Doherty, Neil A. (Journal of Political Economy, 1994)
With asymmetric information, full commitment to long-term contracts may permit markets to approach first-best allocations. However, commitment can be undermined by opportunistic behavior, notably renegotiation. The authors reexamine commitment in insurance markets. They present an alternative model (which extends Jean-Jaques Laffont and Jean Tirole's procurement model to address uncertainty and competition), which involves semipooling in the first period followed by separation. This and competing models (e.g., single-period models and no-commitment models) have different predictions concerning temporal patterns of insurer profitability. A test using California data suggests that some automobile insurers use commitment to attract selective portfolios comprising disproportionate numbers of low risks. Copyright 1994 by University of Chicago Press.